Tax Reporting Assistance based on Law No. 23 of 2018 for Small and Medium Enterprises (SMEs) for Business Sustainability in Yogyakarta - Hilda Octavana Siregar; Faridiah Aghadiati Fajri (Jurnal Pengabdian dan Pengembangan Masyarakat, 2020)
Ordering in fulfilling tax obligations is one measure of the sustainability of a business. But, rules of taxation complexcity and fast changing resulting avoid it specially for small medium enterprises. This community services aim to adding tax ordering for small medium enterprises for fulfilling tax obligations. Rules No 12 Year 2018 is one of the laws that is used as a guideline for SME taxation. The method used is socialization and mentoring of tax report preparation. Through this method, SMEs can fulfill obligations and improve business networks so that they can achieve business sustainability.  The results obtained from this service are an increase in understanding and ability in the preparation of tax reports as outlined in the rubric. The results achieved can be beneficial for SME entrepreneurs and have a positive impact.